The effects of physical refining on the formation of 3-monochloropropane-1,2-diol esters in relation to palm oil minor components - Zulkurnain, Musfirah; Lai, Oi Ming; Latip, Razam Abdul; Nehdi, Imededdine Arbi; Ling, Tau Chuan; Tan, Chin Ping (Elsevier, 2012)
The formation of 3-monochloropropane-1,2-diol (3-MCPD) esters in refined palm oil during deodorisation is attributed to the intrinsic composition of crude palm oil. Utilising D-optimal design, the effects of the degumming and bleaching processes on the reduction in 3-MCPD ester formation in refined palm oil from poor-quality crude palm oil were studied relative to the palm oil minor components that are likely to be their precursors. Water degumming remarkably reduced 3-MCPD ester formation by up to 84%, from 9.79 mg/kg to 1.55 mg/kg. Bleaching with synthetic magnesium silicate caused a further 10% reduction, to 0.487 mg/kg. The reduction in 3-MCPD ester formation could be due to the removal of related precursors prior to the deodorisation step. The phosphorus content of bleached palm oil showed a significant correlation with 3-MCPD ester formation. © 2012 Elsevier Ltd. All rights reserved.